The Gap Between Legal Norms And The Reality Of Human Rights Enforcement Throught The Gamma Case Study In Semarang - Calvin Andika Putra Calvin; Dinda Prama Suari; Savira Sekar Reynata; Artia Nabila Mayangsari (International Journal of Law and Legal Ethics, 2025)
This study explores the phenomenon of extra-judicial killing in Indonesia through the case of Gamma Rizkynata Oktafandy in Semarang as a local reflection of systemic weakness in law enforcement and human rights protection. Although Indonesia has established constitutional and statutory guarantees for the right to life, the implementation of these principles remains inconsistent, revealing a critical gap between normative law and actual practice. Using a qualitative socio-legal approach, this research examines the structural, moral, and cultural factors contributing to the persistence of excessive use of force by law enforcement officers. The findings demonstrate that the Gamma case represents not only individual misconduct but also institutional failure in ensuring accountability and proportionality in state power. The study contributes new insight by linking extra-judicial killing to local socio-legal contexts rather than viewing it solely as a national issue. It concludes that genuine legal reform must involve not only regulatory change but also transformation of the moral awareness and institutional culture of law enforcement agencies to uphold human dignity and substantive justice.